OPTIMALISASI PERAN SERTA LEMBAGA SWADAYA MASYARAKAT DALAM PENANGGULANGAN PEMBERANTASAN TINDAK PIDANA KORUPSI DI KOTA PEKANBARU - Natasya, Audreya; Rahmadan, Davit; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
The impact of corruption is very large, so that it can reduce the quality ofpeople’s welfare in Pekanbaru city, the high state losses due to corruption willcertainly have an impact on the state obligation to provide welfare rights. So the peopleor society will be the victims. For this reason, it is necessary to review the role of thecommunity in preventing corruption as a form of social control that will be able tonarrow the space for corruption and widen the space for anti corruption.This research is a sociological legal research, this is based on field researchwhich refers to interviews and observations statements as well supporting documentsthat have a corelation with the background of the problem to be studied. This study usessecondary date sources consisting of primary, secondary, and tertiary legal materials.This study uses qualitative date analysis by producing a deductive method of drawingconclusions, namely drawing conclusions from that are general to things that arespecific.From the result of the discussion it can be concluded that role of the people ofPekanbaru city in building anti corruption culture is not yet optimal because they donot recive support from all elements of society and also reporting corruption is oftrnintimidated and criminalized by way of reporting back defamation which makes thepepole of Pekanbaru city become afraud to get involved active in eradicating criminalacts of corruption in Pekanbaru city. Therefore it is hoped that the government and lawenforcers in Pekanbaru city must encourage the public to participate in efforts toprevents and eradicate criminal acts of corruption both individually, thourghcommunity organizations, or organizations by providing space to make politicalstatements, make statements thourgh petitions, and anti corruption demonstrations.Keyword : Optimalization, Role of People, Eradication, Corruption Crime